2020
DOI: 10.1126/scitranslmed.aaz5327
|View full text |Cite
|
Sign up to set email alerts
|

Persistently activated, proliferative memory autoreactive B cells promote inflammation in rheumatoid arthritis

Abstract: Autoreactive B cells mediate autoimmune pathology, but exactly how remains unknown. A hallmark of rheumatoid arthritis (RA), a common autoimmune disease, is the presence of disease-specific anticitrullinated protein antibodies (ACPAs). Here, we showed that ACPA-positive B cells in patients with RA strongly expressed T cell–stimulating ligands, produced abundant proinflammatory cytokines, and were proliferative while escaping inhibitory signals. This activated state was found at different degrees in different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…We identified several genes within the NR4A cluster that may facilitate T-B cell interactions including CD69 (which prevents activated lymphocyte egress from SLO), CD86 (a ligand for CD28 on T cells), IL6 (which can promote both APC and T cell interactions), and ICAM1 (which can support B cell interaction with T follicular helper cells) (61). This is also in accord with a recent report showing that tetramer identified ACPA positive B cells in RA blood and synovial fluid express T cell-stimulating ligands and a persistently activated phenotype suggestive of continuous antigenic triggering (62). A key role for B cells in RA flare was also suggested by the recent discovery of a circulating expanded B cell subset (AC2) prior to emergence of a circulating CD45-/CD31-/PDPN+, PRe-Inflammatory MEsenchymal ("PRIME") cell in RA patient blood (21).…”
Section: Discussionsupporting
confidence: 81%
“…We identified several genes within the NR4A cluster that may facilitate T-B cell interactions including CD69 (which prevents activated lymphocyte egress from SLO), CD86 (a ligand for CD28 on T cells), IL6 (which can promote both APC and T cell interactions), and ICAM1 (which can support B cell interaction with T follicular helper cells) (61). This is also in accord with a recent report showing that tetramer identified ACPA positive B cells in RA blood and synovial fluid express T cell-stimulating ligands and a persistently activated phenotype suggestive of continuous antigenic triggering (62). A key role for B cells in RA flare was also suggested by the recent discovery of a circulating expanded B cell subset (AC2) prior to emergence of a circulating CD45-/CD31-/PDPN+, PRe-Inflammatory MEsenchymal ("PRIME") cell in RA patient blood (21).…”
Section: Discussionsupporting
confidence: 81%
“…As the composition of the autoantibody repertoire in serum likely reflects the composition of the autoantibody secreting Bcell compartment (i.e. plasmablasts/plasma cells) [4,42], the predominance of Igλ in the secreted ACPA-IgG repertoire could be explained by selective survival and/or expansion of Igλ-antibody producing B-cell clones. Alternatively, it could be inherent to the citrullinated antigen-binding B-cell repertoire, irrespective of the maturation stage of the B-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Kristyanto H et al. found that ACPA-positive B cells in the blood and synovial fluid of RA patients could secrete the chemokine interleukin 8 to attract neutrophils to the site of inflammation ( 76 ).…”
Section: B Cells In the Pathogenesis Of Ramentioning
confidence: 99%